Discomfort to Comfort, Coconut oil can Reduce Menstrual Pain! - Vaishnavi, K.; Pratiksha, K.; Deepti, K.; Sharon, I.; Jeswel, R.; Maheshwari, J.; Shivani, J.; Sachita, J.; Komal, G.; Anuja, K.; Wansalansha, K.; John, Priyadarsini (International Journal of Nursing Research, 2023)
Background: Menstrual pain usually begins several hours before or just after the onset of menstruation. Women commonly experience pain in the lower abdomen and in some, it radiates to lumbar region, it affects their performance of their daily activities. Coconut oil has many benefits like it is anti-inflammatory and anti-toxin and fights pain directly and also it is cheap as well as it is easily available in home. Aims: The aim of the study was to find the effectiveness of applying coconut oil over lower abdomen in reducing menstrual pain among young women residing in a selected hostel. Materials and Methods: A pre-experimental one group pre-test and post-test study design, using a quantitative approach and non-probability purposive sampling technique on 30 hostlers, participated on the basis of their severity of menstrual pain. The tools deployed include sociodemographic variables, universal pain assessment scale, and modified McGill questionnaire. On the day of the menstrual pain, a selfprepared pre-test questionnaire was administered and after 1 h of intervention the post-test was administered. Both descriptive and inferential statistics were used for the analysis of data. Results: Pre- and post-test and paired-t test were analyzed. The mean ± standard deviations of pre-test were 2.03 ± 1.03 and the post-test was 0.76 ± 0.97. The pain reduced with 1.27 mean differences. The obtained t-value was13.32 and P-value significantly improved at P < 0.00. Conclusion: The study revealed that applying coconut oil over lower abdomen of menstruating women showed improvement in bringing down the level of menstrual pain. This indicates that application of coconut oil effectively reduced the menstrual pain.